Developing occupation-centered programs with the community - Fazio, Linda S. (Slack Incorporated, 2017)
The Third Edition now includes the importance of community asset identification and development toward sustainability. New and updated content on evidence-based practice; program evaluation at multiple levels; funding; non-profits and social entrepreneurship; and trending issues of interest to occupation-centered programmers is provided. New trending issues of interest to programmers include human trafficking, post-combat programming for military veterans and their families, arts-based programming for all ages, and programming to meet current needs of the well-elderly. Developing Occupation-Centered Programs with the Community, Third Edition is an excellent introductory tool for developing occupation-centered programs within the community and is a valuable resource for occupational therapy students at all levels, as well as experienced practitioners in a clinical setting"--